1997
DOI: 10.1897/1551-5028(1997)016<0317:taboam>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Bioaccumulation of a Mixture of Heavy Metals in Chironomus Tentans (Diptera: Chironomidae) in Synthetic Sediment

Abstract: Abstract-This research investigated toxicity and bioaccumulation of a mixture of Cd, Cu, Pb, and Zn in Chironomus tentans in synthetic sediment, and compared predicted to measured steady-state bioaccumulation factors (BAFs). In a toxicity test, C. tentans were exposed to various dilutions of a base concentration (1.0 ϫ) of a mixture of the four metals (5 g/g Cd, 10 g/g Cu, 70 g/g Pb, and 300 g/g Zn) in synthetic sediment. Mortality ranged from 17 to 100%. To measure bioaccumulation of the metals, C. tentans we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
0
21
2
Order By: Relevance
“…For C. tentans larvae exposed for 6 days, the LD 50 for copper and cadmium are 2.5 and 5 ppm, respectively (11). In contrast, as little as 0.1 ppm cadmium or copper induces CTTUB1 in a 1-day exposure.…”
Section: Alpha-tubulin Cdnamentioning
confidence: 98%
See 3 more Smart Citations
“…For C. tentans larvae exposed for 6 days, the LD 50 for copper and cadmium are 2.5 and 5 ppm, respectively (11). In contrast, as little as 0.1 ppm cadmium or copper induces CTTUB1 in a 1-day exposure.…”
Section: Alpha-tubulin Cdnamentioning
confidence: 98%
“…Theoretically, organisms such as aquatic arthropods that experience long-term exposure to the mixtures would be most impacted by such heavy-metal pollution. Interspecific differences in aquatic arthropod populations, including reduced diversity and shifts in benthic community composition at sites located downstream from mining sites, occur in response to heavy-metal pollution (1,4,11). In addition, we previously demonstrated that the population genetic structure of Baetis tricaudatus was also perturbed in the Arkansas River in Colorado, presumably in response to impediments to gene flow in the population caused by mortality arising from exposure to pollution from heavymetal mixtures from mining sites (2).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Larvae of species in the family Chironomidae (Diptera) represent one of the most abundant aquatic insects in most ecosystems, and they have demonstrated their importance as test organisms for studies on risk assessment of substances such as pesticides (Taenzler et al, 2007), heavy metals (Watts and Pascoe, 1996;Harrahy and Clements, 1997;Bechard et al, 2008) and oil (Rosenberg and Wiens, 1976;Cushman, 1984;Crunkilton and Duchrow, 1990;Hatch and Burton Junior, 1999). However, toxicity studies using petroleum-derived products on animals have only been conducted for Amazonian fish (Veintemilla, 2006;Duarte et al, 2010), there being no studies assessing effects on aquatic insects.…”
Section: Introductionmentioning
confidence: 99%